Perempuan Sebagai Pemilih : Isu Utama, Preferensi, dan Dampaknya terhadap Pemilu 2024 - Rusta, Andri; Nafisa, Adinda Charisma; Mahendra, Bagas Islam; Irawati, Irawati; Fajri, Mhd. (Mahesa Research Center, 2024)
This article aims to depict the main issues, political preferences, and the impact of women's participation as voters in the 2024 elections in Indonesia. Through qualitative descriptive research with the methodology of literature review, an analysis is conducted on the conditions of gender equality and sexual violence in Indonesia, considering women's political preferences in legislative and presidential elections, and discussing their impact on the strengthening of democracy in Indonesia. It is found that gender equality and sexual violence issues are the primary focus for women in the 2024 elections. Women's political preferences tend to be influenced by the personality and background of candidates. The participation of women as voters can have a positive impact on creating policies that are responsive to various women's issues. This research also underscores two crucial aspects: the importance of the role of political parties, candidates, and presidential candidates as contestants in elections to present concrete solutions to women's issues packaged in tangible programs or missions. Additionally, this article emphasizes that the success of elections is not only seen in their procedures but also in their substance, which must provide solutions or answers to women's issues in Indonesia.